Mixing characteristics in a hypersonic flow around a transpiration cooled flat plate model - Hermann, T; Ifti, H; McGilvray, M; Doherty, L; Geraets, R (2018)
This paper presents transpiration cooling experiments conducted in the Oxford High Density Tunnel. The flow structure and mixing phenomena between the injected coolant gas and the hypersonic free stream are investigated. A flat plate model is used which is equipped with a gas injection system, four surface mounted heat flux gauges and three surface pressure sensors located downstream of the injection point. Mass injection is realized through a porous ceramic material, and alternatively through a series of slots. Spatially and temporally resolved film effectiveness downstream of the injection point is measured with fast response pressure sensitive paint. The flowfield is visualised by a Z-type Schlieren imaging system. Results show a significant influence of injection on the boundary layer thickness through the additional coolant gas. High blowing ratios can lead to early transition which increases coolant-external flow mixing and leads to a lower film effectiveness. Transpiration cooling requires approximately two orders of magnitude lower blowing ratios to achieve a similar film coverage as in the case of the injection through slots. The film effectiveness increases with an increasing blowing ratio for locations close to the injection point. However, a lower blowing ratio results in a more stable film for locations further downstream.